Characteristic Factors Affecting Oral Pigmentation in Passive Smoker Children - Fahimeh Rashidi Maybodi; Roya Ghafourifard; Mina Mohammad Taheri; Reza Golvardi Yazdi (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Smoking affects not only smokers themselves, but also the people around them. 700 million children are exposed to second hand tobacco worldwide. One of the adverse effects of being a passive smoker is oral pigmentation. Purpose: This study was conducted to evaluate the association between smoking of a parent at home and oral pigmentation in children, and the characteristic factors affecting that. Materials and Method: In this retrospective cohort study, 140 healthy children aged 4 to 10 (mean age= 6.68±1.60), 70 with smoker parent and 70 without smoker parents, were examined for oral pigmentation. Environmental factors were evaluated by asking the parents to fill a questionnaire. Data were analyzed using Chi-square test, Fisher's exact test, Logistic regression, and Spearman scale. Results: There was a meaningful relationship between having a smoker parent and oral pigmentation (p= 0.0001). Spearman's correlation showed parents' duration of cigarette smoking and the number of cigarettes per day could meaningfully affect the severity of oral pigmentation (R=0.329). The study did not find a statistical relationship between oral pigmentation in passive smoking and gender or house area. Conclusion: Children exposed to secondhand tobacco are at more risk for oral pigmentation. Its severity depends on duration of cigarette smoking and the number of cigarettes per day.